The effects of antibiotic disturbance on microbial community stability : Do stress intensity and evolution matter? - Pitkänen, Olli (My University, 2023)
Stable microbial communities have vital roles in various processes. For example, they affect human health and produce a multitude of ecosystem services. Stress-induced alterations in trait distributions in microbial communities may have significant consequences on how communities withstand perturbations. High enough stress intensity may disturb microbial ecosystem stability, which can lead the system to drift into an alternative stable state, thus, potentially changing how these systems function. This thesis aimed to study the effects of antibiotic perturbances on microbial communities. The goals were to discover how the communities’ evolutionary history and stress intensity potentially alter how communities respond to stress. Another aim was also to see if critical transitions (a transition after reaching a tipping point) could be triggered, detected, and ultimately explained. In the experiment, three bacterial communities (differing by evolutionary history) were put under gradually increasing antibiotic disturbances followed by a recovery period. Experiment lasted 70 days. Optical density (OD) was measured every 24 hours and 16S rRNA gene sequencing data from three time points was used to comprise community composition. OD data was used to assess potential tipping points by analysing early warning signals. Community composition data was used to analyse diversity and dissimilarities between samples. The results did not give implications of occurred tipping points. Community compositions between different sample groups and time points were generally similar, and evolutionary history or stress intensity did not seem to cause any systematic trends in altering diversity or increasing dissimilarity. The findings may indicate that individual and community-level antibiotic tolerance played an important role and prevented regime shifts. However, more research (for example, more comprehensive community composition time series) needs to be conducted for further conclusions.
Keywords: microbial community, antibiotics, eco-evo dynamics, stability, tipping point